Analisis Pengaruh Sektor Basis Terhadap Pendapatan Asli Daerah Provinsi DKI Jakarta - Joshua, Steven; Ferdiansyah, Alfian Bagas; Sulistiana, Sulistiana (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2024)
This research aims to identify and analyze leading sectors in DKI Jakarta Province and evaluate their impact on DKI Jakarta Province's Original Regional Income (PAD) during the period 2010 to 2023. This research uses secondary data obtained from BPS DKI Jakarta and the Directorate General of Financial Balance Ministry of Finance, which was then analyzed using the Location Quotient (LQ) method. The results of the analysis show that there are 11 leading sectors in DKI Jakarta Province, namely the Construction sector, Wholesale and Retail Trade, Provision of Accommodation and Food and Drink, Information and Communication, Financial Services and Insurance, Real Estate, Corporate Services, Government Administration, Defense and Social Security Mandatory, Education Services, Health Services and Social Activities, and Other Services. With Pearson Correlation, it is found that all Basic Sectors have a strong influence on increasing PAD in DKI Jakarta Province 2010 – 2023.